2015
DOI: 10.1167/iovs.15-16870
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effect of Resveratrol on Oxidative Stress in Graves' Orbitopathy Orbital Fibroblasts

Abstract: Resveratrol reduced ROS levels and inhibited adipogenesis in GO orbital fibroblasts in vitro. This study supports the potential use of resveratrol in GO treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 46 publications
1
19
0
Order By: Relevance
“…Previously, we have found that quercetin inhibits cigarette smoke extract-induced adipogenesis in GO fibroblasts by reducing ROS (48). Additionally, we have reported several molecules with anti-oxidative properties such as resveratrol, caffeine, and curcumin suppress adipogenesis in GO fibroblasts (49)(50)(51). Given that oxidative stress contributes to the proliferation of orbital fibroblasts (52), the impeded proliferation of GO fibroblasts by PCSK9 inhibition demonstrated in this study may be attributed to the anti-oxidative property of the PCSK9 inhibitor.…”
Section: Discussionmentioning
confidence: 97%
“…Previously, we have found that quercetin inhibits cigarette smoke extract-induced adipogenesis in GO fibroblasts by reducing ROS (48). Additionally, we have reported several molecules with anti-oxidative properties such as resveratrol, caffeine, and curcumin suppress adipogenesis in GO fibroblasts (49)(50)(51). Given that oxidative stress contributes to the proliferation of orbital fibroblasts (52), the impeded proliferation of GO fibroblasts by PCSK9 inhibition demonstrated in this study may be attributed to the anti-oxidative property of the PCSK9 inhibitor.…”
Section: Discussionmentioning
confidence: 97%
“…Based on clinical reports, cigarette smoking-likely the most important environmental factor associated with GO occurrence and progressionmay act, among other mechanisms, by stimulating the generation of ROS and reducing antioxidant production [3,20,21]. In this regard, several in vitro studies demonstrate the therapeutic effectiveness of drugs with antioxidant potential in primary cultured orbital fibroblasts from GO patients [12,[15][16][17]. Clinical studies on the use of antioxidants for the management of GO have also shown them to be clinically effective in patients experiencing mild severity [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…ROS release was determined with 5-(and 6)carboxy-20,70-dichlorodihydrofluorescein diacetate (H2DCFDA; Invitrogen/Thermo Fisher Scientific, Carlsbad, CA, USA), an oxidant-sensitive fluorescent probe, as we described previously [12]. Briefly, primary cultured orbital fibroblasts were pretreated with various concentrations of caffeine for 24 h. The culture medium was then removed, and the cells were washed with PBS, incubated with 10 mM H2DCFDA at 37°C for 30 min, then stimulated with CSE (2%) or H 2 O 2 (10 μM) for 30 min [12,15,16]. The fluorescently stained cells were examined microscopically at 40× and were quantified via flow-cytometric analysis.…”
Section: Intracellular Ros Measurementmentioning
confidence: 99%
“…Orbital fibroblasts subjected to different study conditions were washed with PBS and then lysed with cell lysis buffer on ice. 12 The lysates were centrifuged, and the supernatants were resolved in 10% SDS-polyacrylamide gel electrophoresis (SDS-PAGE), followed by transfer onto polyvinylidene fluoride membranes (Immobilon; Millipore Corp., Billerica, MA, USA). The membranes were then probed with primary antibodies in tris-buffered saline and Tween 20 along with 1% BSA and 0.01% sodium azide.…”
Section: Methodsmentioning
confidence: 99%